Gestaltungsmöglichkeiten der Stadtstaaten bei gegebener Steuersatzautonomie für die Körperschaftsteuer: eine empirische Analyse - Michael Broer (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
German corporated companies are taxed with a federal corporation tax and with a local busi-ness tax. The latter has a similar, but broader tax base (including e.g. 25% of interest pay-ments) and its tax rate is set independently by every municipality including the so called city-states (Stadtstaaten). The federal corporation tax revenue is equally split between the federal government and the federal states (Länder). Till now the federal tax rate has been fixed by the German government. Federal states have not had the right to rule the tax rate of their share of corporation tax. At present a federal commission is discussing whether this should be possible in the future. Once granted this privilege, the city-states will be able to substitute their part of corporation tax by a higher local business tax. Furthermore, because of its broader tax base, there will be a reduction of the statutory tax rate for corporations without a decrease in tax revenue. This paper analyses the revenue effects of this substitution for the city-states taking into account the German fiscal equalization system and the incentive of profit shifting to the city-states. The analysis shows some positive revenue effects to the city-states, if they will substitute their part of corporation tax by a higher local business tax. The revenue effects are subject to different scenarios and add up to 17.5 million for Hamburg, 10.4 million for Berlin and 3.6 million for Bremen.
Keywords: H25; H71; H73; 330; Ländersteuer; Körperschaftsteuer; Großstadt; Gewerbesteuer; Horizontaler Finanzausgleich; Deutschland